Utilização de big data analytics nos sistemas de medição de desempenho: estudos de caso - Mello, Raquel Gama Soares de (2015)
Big data is associated with large amounts of data of different types that come from different sources in a very fast way, able to add value to business and with veracity. Nowadays, many companies are looking for ways to extract useful information from this huge amount of data. This can be attained applying analytical techniques. The application of these techniques to big data is denominated big data analytics. It can influence how managers make their decisions and manage the company businesses. This influences the use of performance measurement systems (PMSs). These systems are composed by a multidimensional set of performance measures that can support decision making and business planning. This way, performance measurement systems and big data analytics can be used to support decision making and the implementation of actions. There is evidence, in the literature, that big data analytics can be used in performance measurement systems. Following this context, this study aims at investigating how companies apply the big data analytics in using performance measurement systems. To achieve this objective, a systematic literature review was carried out for checking existing studies on the relationship between big data and performance measurement system. Then, case study method was applied. The empirical findings showed that big data analytics supports the decision making process, making it more efficient and effective. The results showed that big data analytics helps PMS identify, through analyses, how past actions can influence the future performance. Such analyses are in essence descriptive and predictive and it was applied in sales process. The empirical findings from the case studies showed that big data analytics contributes mainly to the use of PMSs related to planning and to influencing behavior. Therefore, it is possible to conclude that there is a contribution when big data analytics is used in performance measurement system.